A numerical study of forced convection in ideal and randomized reticulated porous structures and a proposal for a new correlation. (March 2022) - Rambabu, S.; Parthasarathy, P.; Ratna kishore, V.
Highlights: Numerical study to investigate the effect of geometry and fluid properties on the convective heat transfer coefficients of reticulated porous media. Reticulated porous structures are modelled using the theoretical Kelvin structure model. A new relationship is proposed to calculate the heat transfer coefficient in reticulated Kelvin structures and in reticulated porous structures in general. The proposed correlation is validated with literature data. Abstract: This paper presents numerical study to calculate convective heat transfer coefficients in reticulated porous media. In this study, the reticulated porous structures are modelled based on theoretical Kelvin model, representing the real porous structures. The geometry of these structures are generated with the help of in-house code and visualisation tool kit (VTK) libraries. The ideal and randomized Kelvin structures are generated for different PPI & porosities. These structures are utilized to calculate the fluid flow and heat transfer for different fluids of different Prandtl numbers (air, water & sea water). By varying the geometrical parameters, the influence of geometries on heat transfer between the flowing fluid and solid phase of open-cell foams are investigated. For this reason, the momentum and energy equations for forced convection in reticulated structures are solved using standard CFD-FVM approach. Based on the simulation outcomes, a new correlation is proposed to calculate the heat transfer coefficients in the reticulated porous structures. The proposed correlation is validated by comparing it with numerical and experimental data of real reticulated porous structures available in the literature. The effects of the Colburn j factor and performance factor are also computed to obtain the best outcome.